FEMA 310 Tier 1 seismic evaluation of existing building: A case study of a 7-story academic RC building of Jenderal Soedirman University, Indonesia. Issue 1 (December 2020) - Haryanto, Yanuar; Hu, Hsuan-Teh; Widyaningrum, Arnie; Alfidiah, Esya; Hidayat, Banu Ardi
Abstract: A need to predict the seismic vulnerability of current buildings has led to a heightened interest in study that deals with seismic vulnerability assessment methods. The easiest and fastest method, known as a walk-down survey or a street survey, involves just the superficial information accumulated during a short inspection of a building. This paper picks a fairly new seven-story academic building made of reinforced concrete (RC) located at the Jenderal Soedriman University in Purwokerto, Indonesia, which was designed in 2015 using construction details illustrative of that exact period, for FEMA 310 Tier 1 assessment in the context of Performance-Based Earthquake Engineering (PBEE). Mandatory checklists as a role of the region of seismicity and the building's level of performance are done. The outcomes after a procedure projected the building in the case-study demonstrated a range of possible flaws and seismic vulnerability. Therefore, detailed comprehensive evaluation is intensely endorsed.